The Effectiveness Of Vitamin D Provision On The Expression Of Fibroblast Growth Factor-2 Under The Orthodontic Mechanical Stress In Pregnant Wistar Rat (Rattus Norvegicus) - Ari Triwardhani, - (2020)
Female patients have the possibility of pregnancy in the course of fixed orthodontic treatment. Pregnant women are often advised by physician to consume various kinds of nutritional support vitamins for the mother and fetus contained, one of which is vitamin D. The outcome of this research is to examine the effectiveness of vitamin D provision on the fibroblast growth factor-2 (FGF-2) expression during orthodontics mechanical stress (OMS) in pregnant wistar rats (Rattus Novergicus). Healthy pregnant Wistar rats (R. novergicus) 16-20 weeks-old, 200-250 grams body weight then grouped randomly into 4 groups; control group: pregnant rats administered vitamin D without OTM (K7 and K14) and treatment group: pregnant rats with OTM and vitamin D administration (P7 and P14). Nickel Titanium (NiTi) closed coil spring was installed among upper central incisor to the upper first molar to induce OMS with 10g/mm2 force. After 7 days or 14 days all animals were sacrificed for pre-maxilla extraction. Immunohistochemically examination was carried out to examine FGF-2 expression in the tension and compressed side. The lowest expression of FGF-2 was found in the P7 group in the tension side (4.7±2.39) and compression side (4.31±1.7). There was no significant difference between groups in the FGF-2 expression on the tension side (p=0.28;p>0.05) and compression side (p=0.14; p>0.05). The vitamin D provision during OMS in pregnant wistar rats (R. novergicus) had no significant effect on the expression of FGF-2.